Distinct trajectories in HbA1c are associated with different all-cause mortality and morbidity in newly diagnosed patients with type 2 diabetes. Issue 5 (October 2020) - Hemo, Beatriz; Geva, Dikla; Shahar, Danit R.; Golan, Rachel; Heymann, Anthony D.
Highlights: From diagnosis, patients can be categorized into two distinct HbA1c trajectories. Patients in the sharp-incline trajectory had a higher risk for all-cause mortality. Estimation of HbA1c trajectory early in the disease is a good prognostic indicator. Categorization by trajectory can identify patients in need of intensive follow up. Abstract: Aims: To identify trajectories of long-term HbA1c levels and examine associations with subsequent risk for morbidity and mortality. Methods: We conducted a longitudinal follow-up among 27, 724 patients, newly diagnosed with type 2 diabetes, in a large healthcare organization. We identified trajectories of long-term HbA1c levels during the first 5 years post diabetes onset to examine associations with subsequent risk for morbidity and all-cause mortality. Results: We identified two HbA1c trajectories; the "Steady-plateau HbA1c trajectory" in 93% of patients and a "Sharp-incline HbA1c trajectory" in 7% of patients. When compared to the steady-plateau group, patients in the sharp-incline group were younger, male, from a lower socio-economic background, and higher levels of HbA1c at baseline. Patients in the sharp-incline trajectory had a HR = 1.83 (95%CI: 1.58–2.12) for all-cause mortality, HR = 1.99 (95%CI: 1.74–2.27) for cardiovascular disease, and HR = 1.68 (95%CI: 1.51–1.86) for renal disease, compared to patients in the steady-plateau trajectory. Conclusions: Patients in the sharp-incline trajectory had a higher risk for all-cause mortality, cardiovascular disease, and renal disease, compared to patients in the steady-plateau trajectory. Estimation of HbA1c variability in the first years of diagnosis may be a useful indicator of those patients at high risk for diabetes related complications.